Adhesive Tissue Engineered Scaffolds: Mechanisms and Applications - Chen, Shuai; Gil, Carmen J.; Ning, Liqun; Jin, Linqi; Perez, Lilanni; Kabboul, Gabriella; Tomov, Martin L.; Serpooshan, Vahid (Frontiers in Bioengineering and Biotechnology, 2021)
A variety of suture and bioglue techniques are conventionally used to secure engineered scaffold systems onto the target tissues. These techniques, however, confront several obstacles including secondary damages, cytotoxicity, insufficient adhesion strength, improper degradation rate, and possible allergic reactions. Adhesive tissue engineering scaffolds (ATESs) can circumvent these limitations by introducing their intrinsic tissue adhesion ability. This article highlights the significance of ATESs, reviews their key characteristics and requirements, and explores various mechanisms of action to secure the scaffold onto the tissue. We discuss the current applications of advanced ATES products in various fields of tissue engineering, together with some of the key challenges for each specific field. Strategies for qualitative and quantitative assessment of adhesive properties of scaffolds are presented. Furthermore, we highlight the future prospective in the development of advanced ATES systems for regenerative medicine therapies.